Incidence and determinants of hypophosphatemia in diabetic ketoacidosis: an observational study. Issue 1 (17th February 2021) - van der Vaart, Amarens; Waanders, Femke; van Beek, André P; Vriesendorp, Titia M; Wolffenbutel, B H R; van Dijk, Peter R
Abstract : Introduction: Diabetic ketoacidosis (DKA) is a life-threatening complication of type 1 diabetes mellitus (T1DM) characterized by hyperglycemia and metabolic acidosis. Hypophosphatemia in DKA often occurs during hospital admittance for DKA. Literature on the magnitude, determinants and consequences of hypophosphatemia in DKA is scarce. Primary aim of this study was to investigate the incidence and consequences of hypophosphatemia during hospitalisation for DKA. Research design and methods: Cohort study among individuals with T1DM who were admitted for DKA between 2005 and 2020 in an academic and a non-academic hospital. Multivariate regression models were performed to investigate determinants of the lowest phosphate during the treatment of DKA. Results: A total of 127 episodes of DKA among 80 individuals were identified. Age at DKA presentation was 28 (22–46) years, 45% of the cases was female, diabetes duration was 13.2 (8.9–25.5) years with glycosylated hemoglobin levels of 91.9±26.2 mmol/mol. In 9% of all cases, DKA was the first presentation of T1DM. Lowest phosphate levelss reported during the treatment phase were 0.54 (0.32–0.83) mmol/L and hypophosphatemia was present in 74% (62/84). The time to lowest phosphate was 16 (8–23) hours. In multivariate analysis, baseline bicarbonate and hemoglobin at admission were significantly associated with the lowest phosphate level reported. No adverse effects of hypophosphatemia on hospital stay duration, morbidity or mortality were found, even if left untreated. Conclusions: Hypophosphatemia during DKA is common and increases with severe acidosis. However, in this study it was not related to adverse outcomes. Although limitations of this retrospective study should be taken into account, the routine and repeated measurement of phosphate levels in DKA could be reconsidered, provided that possible symptoms related to hypophosphatemia are monitored.